1993
DOI: 10.1002/gcc.2870080409
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in non‐small cell lung cancer pleural effusions: Cytogenetic indicators of disease subgroups

Abstract: A cytogenetic study of pleural effusions (PE) containing metastatic or invasive tumor cells from 11 patients with non-small cell lung cancer (NSCLC) (3 squamous cell carcinomas [SQC] and 8 adenocarcinomas [ADC] including 1 giant cell variant) was performed to identify non-random chromosome abnormalities. Numerical abnormalities seen in > or = 30% of cases included gain of chromosomes 7 and 20, and loss of chromosomes 4, 9, 10, 13, 15, 16, 18, 19, 21, and 22. The most frequent structural abnormality involved re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…Gains of genetic material in the long arm of chromosome 8 are not often found in cytogenetic analyses. However, the presence of isochromosome 8q has been associated with primary adenocarcinomas (Jin et al, 1988) and gains in 8q have been reported to be frequent in pleural effusions from NSCLC patients (Lukeis et al, 1993). In our CGH analysis, this particular aberration (including three high-level amplifications) occurred in 65% of the informative tumours.…”
Section: Discussionmentioning
confidence: 59%
“…Gains of genetic material in the long arm of chromosome 8 are not often found in cytogenetic analyses. However, the presence of isochromosome 8q has been associated with primary adenocarcinomas (Jin et al, 1988) and gains in 8q have been reported to be frequent in pleural effusions from NSCLC patients (Lukeis et al, 1993). In our CGH analysis, this particular aberration (including three high-level amplifications) occurred in 65% of the informative tumours.…”
Section: Discussionmentioning
confidence: 59%
“…The terms 'allelic imbalance', 'loss of heterozygosity' and 'allelespecific deletions' are used equally because cytogenetic studies have rarely shown lp amplification in NSCLC, whereas deletions have been found (Testa and Siegfried, 1992;Lukeis et al, 1993). Furthermore, gene LMYC (lp32) is rarely amplified (< 1%) in these tumours (Yokota et al?…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis has shown frequent structural rearrangements at lpl3 (Testa and Siegfried, 1992;Lukeis et al, 1993;Johansson et al, 1994). Balanced translocations seemed to be relatively rare in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lines PL27 and L162 (Lukeis et al, 1993) were obtained from Dr S Hasthorpe (Royal Childrens Hospital, Melbourne) and maintained as for COS cells. Other cell lines were obtained from ATCC.…”
Section: Cell Lines and Culturementioning
confidence: 99%